2005
DOI: 10.1002/jso.20369
|View full text |Cite
|
Sign up to set email alerts
|

Tumor budding and evidence-based treatment of T2 rectal carcinomas

Abstract: A number of tumor budding may be useful for determining the individualized treatment of T2 rectal carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…There is a strong association between budding and the presence of lymph node metastases and lymphovascular invasion, 11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] defined by the presence of tumor cells within an endothelium-lined space, and it has been suggested that buds represent the part of the tumor that has gained the ability to invade lymphatics and vascular channels. This idea is supported by two intriguing morphological studies: Morodomi et al 33 examined serial sections of high-budding areas to demonstrate that budding nests are often found adjacent to areas of lymphovascular space invasion, and, in a more recent study, Ohtsuki et al 31 performed double staining for anti-cytokeratin antibodies and anti-lymphatic antibodies, finding that a number of 'buds' at the invasive edge of a tumor are in fact located in small lymphatic spaces.…”
Section: Morphological Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a strong association between budding and the presence of lymph node metastases and lymphovascular invasion, 11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] defined by the presence of tumor cells within an endothelium-lined space, and it has been suggested that buds represent the part of the tumor that has gained the ability to invade lymphatics and vascular channels. This idea is supported by two intriguing morphological studies: Morodomi et al 33 examined serial sections of high-budding areas to demonstrate that budding nests are often found adjacent to areas of lymphovascular space invasion, and, in a more recent study, Ohtsuki et al 31 performed double staining for anti-cytokeratin antibodies and anti-lymphatic antibodies, finding that a number of 'buds' at the invasive edge of a tumor are in fact located in small lymphatic spaces.…”
Section: Morphological Featuresmentioning
confidence: 99%
“…11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] On multivariate analysis, budding has consistently emerged as an independent adverse prognostic factor, associated with local tumor recurrence and distant metastases, and significantly worse overall and disease-free survival. 12,15,16,21,27,28,31,32,[34][35][36]38,40,41 The adverse prognostic impact of high-grade tumor budding is seen in both early and advanced colorectal carcinoma, and there are several scenarios in which this feature might influence clinical decision making, particularly in early colorectal carcinoma.…”
Section: Clinical Significance Of Tumor Buddingmentioning
confidence: 99%
See 2 more Smart Citations
“…Various elaborate systems for quantification of tumor budding in colorectal cancer have been described. 3,8,[11][12][13][14][15][16][17][18][19] All of these tumor budding grading systems share an association of high peri-tumoral budding with a worse outcome.…”
mentioning
confidence: 99%